Tubulin detyrosination shapes Leishmania cytoskeletal architecture and virulence - Rosa Milagros Corrales; Jeremy Vincent; Lucien Crobu; Rachel Neish; Binita Nepal; Julien Espeut; Grégoire Pasquier; Ghislain Gillard; Chantal Cazevieille; Jeremy C. Mottram; Dawn M. Wetzel; Yvon Sterkers; et al. (Proceedings of the National Academy of Sciences, 2025)
Tubulin detyrosination has been implicated in various human disorders and is important for regulating microtubule dynamics. While in most organisms this modification is restricted to α-tubulin, in trypanosomatid parasites, it occurs on both α- and β-tubulin. Here, we show that in Leishmania , a single vasohibin (LmVASH) enzyme is responsible for differential kinetics of α- and β-tubulin detyrosination. LmVASH knockout parasites, which are completely devoid of detyrosination, show decreased levels of glutamylation and exhibit a strongly diminished pathogenicity in mice, correlating with decreased proliferation in macrophages. Reduced virulence is associated with altered morphogenesis and flagellum remodeling in detyrosination-deficient amastigotes. Flagellum shortening in the absence of detyrosination is caused by hyperactivity of a microtubule-depolymerizing Kinesin-13 homolog, demonstrating its function as a key reader of the trypanosomatid-tubulin code. Taken together, our work establishes the importance of tubulin detyrosination in remodeling the microtubule-based cytoskeleton required for efficient proliferation in the mammalian host. This highlights tubulin detyrosination as a potential target for therapeutic action against leishmaniasis.